Studi Implementasi Sistem Rujukan Berjenjang Antar Fasilitas Kesehatan Tingkat Lanjut di Era JKN di Provinsi Sulawesi Selatan - Nur Arifah; Rini Anggraeni; Adelia U. A. Mangilep (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2021)
One of the determinants of achieving quality control and cost control is the implementation of tiered referral health. This research was motivated by the absence of research on the implementation of referrals from FKTP to FKTL. Data from RSUP Dr. Wahidin Sudirohusodo’s annual report showed in 2015 and first half of 2016, >60% cases in class A hospital were level 1 severity case which should still be handle in class D and C hospitals. This affects the accumulation of patiens in tertiary hospitals and inefficient use of resources. It is a qualitative research with phenomenology approach to determine the implementation of a tiered referral system between advanced health facilities in JKN era in South Sulawesi. The results shows most of referral were made due to facilities limitation and inavailability of specialist. There were referrals which made based on patients requests not based on clinical reasons. It is also found hospital staff who did not know about the existing of standard operational procedure of referral in the hospital. Some hospital staff has no knowledge on the referral regulation nor about hospital classification. This research is expected to be able to contribute to the development of science and can be used as input for hospitals and BPJS in an effort to improve the optimization of tiered referral services. Based on the results of the study it is recommended to improve facilities and infrastructure that can support the provision of referral services in hospitals.